Physical conditions for the formation of gabbros and migmatites derived from mafic rocks in the center of Sierra de Valle Fértil, San Juan - Tibaldi, A.M. (2009)
A sequence of plutonic mafic rocks inter-stratified with both mafic- and metasedimentary-derived migmatites is found along the San Juan valley in the center of the Sierra de Valle Fértil. This natural example shows the transition from igneous to metamorphic petrologic processes which occurred during the crystallization of mafic magmas and the subsequent partial melting of crystallized gabbroic rocks. This work studies the mineralogical changes associate to this petrologic transition. Thermobarometric estimates based on amphibole-plagioclase indicate that the mafic magmas crystallized at around 1100°C and 5 ± 0.5 kbar. The conditions under which gabbroic rocks were partially melted are estimated using two pyroxenes ther-mometry and amphibole-plagioclase thermobarometry. Similar physical conditions in the range between 740 and 840°C and 5 to 6.5 kbar are recovery from mineral assemblages in the mesosomes and leucosomes of mafic migmatites. The main mineral compositional changes that accompanied the partial process of the gabbroic rocks are: 1) depletion of aluminium content and Mg# ratio in pyroxenes; 2) depletion of anorthite mole fraction of the plagioclases; and 3) depletion of the Mg# ratio in amphiboles. These mineral compositional variations are consistent with those found by experimentally melting mafic protoliths. Experimental results showed that the temperature for promoting amphibole-dehydration melting in mafic proto-liths is of around 850°C, whereas the addition of an aqueous fluid would lower the melting temperature to around 800°C. Combining field relationships, textural features, mineral compositional variations and thermo-barometric estimates with experimental results, we demonstrated that the transition from igneous mafic rocks to mafic migmatites was due to isobaric cooling. Moreover, repetitive intrusion of mafic magmas sustained the sequence at granulite-facies conditions, so avoiding rapid cooling. The natural case from the centre of the Sierra de Valle Fértil is interpreted to expose an example of the plutonic-me-tamorphic core of the Famatinian magmatic arc, where the abnormally high metamorphic gradient provide evidence that large volume of mafic magmas reached and emplaced at paleodepths of between 16 and 20 kilometres.